Relação entre materiais dentários e o complexo dentino-pulpar - Hebling, Josimeri [UNESP]; Ribeiro, Ana Paula Dias [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (My University, 2010)
Despite the strong valorization of the esthetics and its relationship with restorative materials, the biological principles of any clinical procedure are extremely important to maintain the vitality of the dentin-pulp complex. Dentin and pulp tissue are susceptible to different kinds of irritants such as toxins from microorganisms, traumatic procedures of cavity preparation, as well as toxic components released by restorative materials applied in non recommended clinical situations. Initially, the pulp responds to irritation by starting an inflammatory reaction which involves outward movement of dentinal fluid and intratubular deposition of immunoglobulins, upregulation of odontoblast activities, presence of immune cells and their cytokines as well as local expression of neuropeptides and chemokines. After these initial events, the inflammation process can be resolved associated or not to sclerotic dentin formation and reactionary dentin deposition. If high intensity offensive stimuli are applied to the dentin-pulp complex, death of odontoblasts takes place and consequently pulp ageing or even partial necrosis of this tissue may occurs. Thereby, clinicians need to be aware about the physiological and pathological features of the dentin-pulp complex as well as the possible biological consequences of different clinical procedures. In this way, the dentists should be able to carry out minimally aggressive operative techniques and to select the more appropriate restorative materials for each specific clinical situation in order to obtain excellent clinical results associated to the maintenance of pulp vitality.

Mesmo diante da valorização dos princípios estéticos e mecânicos dos materiais restauradores, os fatores biológicos são de extrema importância para a manutenção da vitalidade do complexo dentino-pulpar e devem ser levados em consideração para se obter o sucesso dos procedimentos clínicos. A dentina e tecido pulpar estão susceptíveis a diversos tipos de agressores que vão desde toxinas derivadas de microrganismos até aqueles originados por preparos cavitários erroneamente executados e materiais dentários tóxicos. Inicialmente, a polpa reage desencadeando um processo inflamatório que envolve fluido dentinário, odontoblastos, células do sistema imune e suas citocinas inflamatórias, além de neuropeptídeos e quimiocinas. Posteriormente poderá ocorrer resolução do quadro inflamatório, esclerose dentinária associada ou não a formação de dentina reacional ou reparadora. Caso a agressão seja de alta intensidade ou persista por um período longo, poderá ocorrer morte dos odontoblastos com consequente envelhecimento pulpar ou até mesmo necrose desse tecido conjuntivo especializado. Sendo assim, é de extrema importância o conhecimento dos aspectos fisiológicos e patológicos da polpa dentária assim como das conseqüências das intervenções realizadas diariamente na clínica. Dessa forma, o profissional poderá executar uma técnica operatória minimamente agressiva e selecionar materiais dentários adequados para serem utilizados dentro de cada situação clínica específica, visando à manutenção da integridade do complexo dentino-pulpar.
Relationship between dental materials and the dentin-pulp complex
Keywords: Dental Pulp Capping; Dental Materials; Biocompatibility Test; Capeamento da Polpa Dentária; Materiais dentários; Teste de biocompatibilidade